Inferior Phrenic Arteries Originating from the Celiac Artery with a Common Trunk - ARİFOĞLU, YASİN; Yıldırım, Mehmet; Balcıoğlu, Hüseyin; ARİFOĞLU, YASİN (My University, 2013)
The inferior phrenica artery (IPA), which arises from the abdominal aorta just distal to the aortic hiatus, may arise from different sites. Although comprehensive analyses of the IPA are described in other populations, the rates of the variations of the origins are not well elucidated in Turkish people. In this study, we report IPA arising as a common trunk from the abdominal aorta. This finding in a 52 year old male cadaver was noticed during a routine dissection for students in the 2010-2011 academic year. We believe this report is a valuable contribution to the literature on variation of the phrenic arteries and is of interest to clinicans in the surgical and interventional radiological procedures of the adrenal glands, spleen, liver and stomach as well as to the educators of anatomy.
Keywords: Abdominal aorta; celiac artery; inferior phrenic artery; variation